Piezoelectric micropump with nanoliter per minute flow for drug delivery systems - Juliana Johari,; Jumril Yunas,; Azrul Azlan Hamzah,; Burhanuddin Yeop Majlis, (Universiti Kebangsaan Malaysia, 2011)
Piezoelectric Actuated Valveless Micropump (PAVM) has been designed and successfully fabricated using MEMS fabrication processes. The micropump uses a PZT: Pb(ZrTi)Ox ceramic plate to actuate a silicon membrane which bends when a voltage is applied to the piezoelectric actuator. The resultant reciprocating movement of the pump membrane is then converted into pumping effect. By integrating dynamic passive valves into the device, the pump would then operate continuously with volumetric pumping rate determined by the frequency of the driving voltage. Simulation work to determine the micropump fluidic characteristics was performed using CoventorWare MemFSI™ module. The pump was fabricated on a double side polished silicon wafer via simple two-mask micromachining process. The fabricated micropump, having an outer dimension of 14 mm × 14 mm × 2 mm, was then tested with DI (deionized) water as the test liquid. A driving voltage of 16 Vpp was applied to the PZT actuator. Pump rate of 4.98 nL per min was obtained at 0.673 kHz. The fabricated micropump envisages a promising pumping method to be implemented into drug delivery systems.